SUSTAINABLE TOURISM DI PANTAI KUTA BALI DALAM PERSEPSI WISATAWAN (Survei terhadap Wisatawan Mancanegara {Australia, Cina dan Jepang} yang berkunjung Pantai Kuta Bali) - Aldira, Chaerul; Wibowo, Lili Adi; Yuniawati, Yeni (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
This research aimed to analyze the effort to create sustainable tourism towards tourist motivation and behavior in Kuta Beach Bali. Sustainable tourism consists of environmental dimensions, economic dimensions, socio-cultural dimensions, and level of tourist satisfaction. This research employed descriptive method and explanatory survey with size of 103 samples of tourist from Australia, China, and Japan who have visited Kuta Beach Bali. The data were collect through interviews, observations, questionnaires, and documentation. It utilized data analysis technique of SEM (Structural Equation Model) Analysis. The result of the study showed that the variables of tourist motivation present significant influence towards tourist behavior in Kuta Beach Bali, and tourist behavior is influencing significantly towards creating sustainable tourism in Kuta Beach Bali.